Dietary Supplementation With Medium-Chain Triglycerides Reduces Candida Gastrointestinal Colonization in Preterm Infants. Issue 2 (February 2019) - Arsenault, Amanda B.; Gunsalus, Kearney T. W.; Laforce-Nesbitt, Sonia S.; Przystac, Lynn; DeAngelis, Erik J.; Hurley, Michaela E.; Vorel, Ethan S.; Tucker, Richard; Matthan, Nirupa R.; Lichtenstein, Alice H.; Kumamoto, Carol A.; Bliss, Joseph M.
Abstract : Background: Candida is an important cause of infections in premature infants. Gastrointestinal colonization with Candida is a common site of entry for disseminated disease. The objective of this study was to determine whether a dietary supplement of medium-chain triglycerides (MCTs) reduces Candida colonization in preterm infants. Methods: Preterm infants with Candida colonization (n = 12) receiving enteral feedings of either infant formula (n = 5) or breast milk (n = 7) were randomized to MCT supplementation (n = 8) or no supplementation (n = 4). Daily stool samples were collected to determine fungal burden during a 3-week study period. Infants in the MCT group received supplementation during 1 week of the study period. The primary outcome was fungal burden during the supplementation period as compared with the periods before and after supplementation. Results: Supplementation of MCT led to a marked increase in MCT intake relative to unsupplemented breast milk or formula as measured by capric acid content. In the treatment group, there was a significant reduction in fungal burden during the supplementation period as compared with the period before supplementation (rate ratio, 0.15; P = 0.02), with a significant increase after supplementation was stopped (rate ratio, 61; P < 0.001). Fungal burden in the control group did not show similar changes. Conclusions: Dietary supplementation with MCT may be an effective method to reduce Candida colonization in preterm infants. Abstract : Supplemental Digital Content is available in the text.